Problem Based Learning (PBL) Model on Grade 5 Science Learning Outcomes in Elementary Schools: Model Problem Based Learning (PBL) Terhadap Hasil Belajar IPA Kelas 5 di Sekolah Dasar - Ramadhani, Mifta Aulia; Shofiyah, Noly (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the learning outcomes before and after the application of the Problem Based Learning (PBL) model and to determaine the effect of the Problem Based Learning (PBL) model on the cognitive learning outcomes of fifth grade science at SDN Candinegoro. The research method used is quantitative with the type of pre-experimental research and the design uses a one-grup pretest posttest design. The population of this study were all 32 grade students of SDN Candinegoro. The sample was taken using saturated sampling. Data collection techniques used in the form of tests and research instruments in the form of pretest and posttest sheets. The results showed that (1) learning outcomes before the application of the PBL model obtained an average of 39 with low achievement categories, learning outcomes after the application of PBL obtained an average of 81 with very high categories, (2) The results of the N-Gain calculation before an after the application of the model show a moderate effect, then the percentage classically the acquisition of N-Gain of 0,71% gets the medium category.